Development of Learning Model -Project-Based Service Learning (PJBSL) for Information Literacy Course - Marlini; Z. Mawardi Efendi; Darmansyah (International Journal on Integrated Education, 2022)
This research is motivated by the need for a project-based service-learning (PjBSL) model for information literacy courses in universities through needs analysis. The learning model applied is not optimal, causing students' information literacy skills to be below, one of which can be seen in the low information literacy skills of students and student learning outcomes. This study aims to develop a project-based learning model and a service-learning blend of PjBL and SL that is valid, practical, and effective to improve student learning outcomes. The research design used is Research & Development (R & D) using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model to develop the PjBSL learning model and its supporting components such as model guidebooks, lecturer guides, and student guides. The subjects in the study were lecturers and students of PS-PII-FBS-UNP. The results showed that the PjBSL model developed in the information literacy course was declared to have very high validity and practicality.